International Spillovers of Macroeconomic Shocks : A Quantitative Exploration - Laxton, Douglas (IMF Working Papers; Working Paper, 2000)
This paper provides a quantitative exploration of international spillovers of macroeconomic shocks among the major industrial economies. The particular topical example analyzed here concerns the possible effects on the industrial economies of adverse shocks to the current U.S. economic expansion. The potential spillover effects of U.S. shocks to other industrial economies are found to be quite large. Extant economic conditions, particularly the low levels of nominal interest rates and the consequent possibility of liquidity traps in countries such as Japan, could significantly magnify these spillover effects.